Multifunctional Single‐Site Catalysts for Alkoxycarbonylation of Terminal Alkynes. Issue 17 (17th August 2016) - Chen, Xingkun; Zhu, Hejun; Wang, Wenlong; Du, Hong; Wang, Tao; Yan, Li; Hu, Xiangping; Ding, Yunjie
Abstract: A multifunctional copolymer (PyPPh2 –SO3 H@porous organic polymers, POPs) was prepared by combining acidic groups and heterogeneous P, N ligands through the copolymerization of vinyl‐functionalized 2‐pyridyldiphenylphosphine (2‐PyPPh2 ) and p ‐styrene sulfonic acid under solvothermal conditions. The morphology and chemical structure of the copolymer were evaluated using a series of characterization techniques. Compared with traditional homogeneous Pd(OAc)2 /2‐PyPPh2 / p ‐toluenesulfonic acid catalyst, the copolymer supported palladium catalyst (Pd–PyPPh2 –SO3 H@POPs) exhibited higher activity for alkoxycarbonylation of terminal alkynes under the same conditions. This phenomenon could be attributed to the synergistic effect between the single‐site Pd centers, 2‐PyPPh2 ligands, and SO3 H groups, the outstanding swelling properties as well as the high enrichment of the reactant concentration by the porous catalyst. In addition, the catalyst could be reused at least 4 times without any apparent loss of activity. The excellent catalytic reactivity and good recycling properties make it an attractive catalyst for industrial applications. This work paves the way for advanced multifunctional porous organic polymers as a new type of platform for heterogeneous catalysis in the future. Abstract : Multifunctional catalyst ! A novel multifunctional copolymer [(PyPPh2 –SO3 H@porous organic polymers (POPs), Py=pyridine] is used as a support to prepare a heterogeneous palladium catalyst (Pd–PyPPh2 –SO3 H@POPs). The multifunctional catalyst exhibits higher activity than the corresponding homogeneous catalyst for alkoxycarbonylation of terminal alkynes. The high efficiency is attributed to the synergistic effect of the Pd center, 2‐PyPPh2, ligand and SO3 H group, which was strengthened by the high concentration of the ligand and SO3 H groups on the copolymer.